2009
DOI: 10.1002/dat.20367
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in dialysis patients and its effect on various disease markers

Abstract: Longitudinal linkages between intentional exposure to x‐rated material and sexually aggressive behavior were examined among youth 10–15 year olds surveyed nationally in the United States. At Wave 1 in 2006, participants (n = 1,588) were queried about these exposures and outcomes in the preceding 12 months. Wave 2 data (n = 1,206) were collected approximately 12 months after Wave 1 and Wave 3 data (n = 1,159) were collected approximately 24 months after Wave 1. Thus, data for this project represent a 36‐month t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The substantial variation in 25(OH)D concentration between individuals and groups could be a result of factors that include latitude, skin pigmentation, vitamin D intake from food and supplements, and sun protection culture (Holick, ). In addition, there is a range of factors specific to dialysis patients that may further explain the aetiology of vitamin D deficiency/insufficiency in this group, in particular but not limited to lower dietary intake (Korkor et al ., ), possibly as a result of dietary restrictions and decreased appetite; limited mobility and time outdoors (Clayton & Singer, ; Korkor et al ., ); reduced synthesis of cholecalciferol in the skin as a result of reduced glomerular filtration rate (Michaud et al ., ); and losses in the peritoneal fluid (Sahin et al ., ). However, the evidence discriminating between dietary and sun exposure sources of vitamin D is scant.…”
Section: Introductionmentioning
confidence: 99%
“…The substantial variation in 25(OH)D concentration between individuals and groups could be a result of factors that include latitude, skin pigmentation, vitamin D intake from food and supplements, and sun protection culture (Holick, ). In addition, there is a range of factors specific to dialysis patients that may further explain the aetiology of vitamin D deficiency/insufficiency in this group, in particular but not limited to lower dietary intake (Korkor et al ., ), possibly as a result of dietary restrictions and decreased appetite; limited mobility and time outdoors (Clayton & Singer, ; Korkor et al ., ); reduced synthesis of cholecalciferol in the skin as a result of reduced glomerular filtration rate (Michaud et al ., ); and losses in the peritoneal fluid (Sahin et al ., ). However, the evidence discriminating between dietary and sun exposure sources of vitamin D is scant.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The pathophysiologic mechanisms underlying vascular access complications are poorly understood. 10 Due to the block in conversion from 25(OH)D to active 1,25D in ESRD, 1,25D or its analogs are frequently administered to patients with ESRD to overcome these adverse effects. Our prior work suggests mineral metabolism may be an important target for intervention but confirmatory studies are needed.…”
Section: Introductionmentioning
confidence: 99%
“…9 Deficiency of 25(OH)D is common among patients with ESRD, with some studies estimating the prevalence above 80%. 10 Due to the block in conversion from 25(OH)D to active 1,25D in ESRD, 1,25D or its analogs are frequently administered to patients with ESRD to overcome these adverse effects. Nonetheless, 25(OH)D may be locally converted in tissues or have other direct effects, and recent studies suggest that low 25(OH)D associates with mortality in HD patients in meta-analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient vitamin D intake can contribute to serum vitamin D deficiency, which is highly prevalent in the haemodialysis population 44 . The high prevalence of vitamin D deficiency in individuals receiving haemodialysis is multifactorial but insufficient sunlight exposure 45,46 , reduced dietary intake 46 , and reduced skin synthesis 47 are all believed to play a role. It has been shown that vitamin D deficiency results in a series of adverse complications, including cardiovascular disease 48 , osteoporosis and fractures 49 , ultimately leading to a high mortality risk in this population [50][51][52][53] .…”
mentioning
confidence: 99%